Lower quarter Y balance test performance: Reference values for healthy youth aged 10 to 17 years - Schwiertz, G.; Brueckner, D.; Beurskens, R.; Muehlbauer, T. (Gait and Posture, 2020)
Background The Lower Quarter Y Balance Test (YBT-LQ) has been widely used to register dynamic balance performance in children and adolescents. However, studies evaluating age- and sex-specific normative data to assess and classify YBT-LQ performance for these age-cohorts are missing.